Are large simple trials for dementia prevention possible?. (12th December 2019) - Whiteley, William N; Anand, Sonia; Bangdiwala, Shrikant I; Bosch, Jackie; Canavan, Michelle; Chertkow, Howard; Gerstein, Hertzel C; Gorelick, Philip; O'Donnell, Martin; Paré, Guillaume; Pigeyre, Marie; Seshadri, Sudha; et al.
Abstract: New trials of dementia prevention are needed to test novel strategies and agents. Large, simple, cardiovascular trials have successfully discovered treatments with moderate but worthwhile effects to prevent heart attack and stroke. The design of these trials may hold lessons for the dementia prevention. Here we outline suitable populations, interventions and outcomes for large simple trials in dementia prevention. We consider what features are needed to maximise efficiency. Populations could be selected by age, clinical or genetic risk factors or clinical presentation. Patients and their families prioritise functional and clinical outcomes over cognitive scores and levels of biomarkers. Loss of particular functions or dementia diagnoses therefore are most meaningful to participants and potential patients and can be measured in large trials. The size of the population and duration of follow-up needed for dementia prevention trials will be a major challenge and will need collaboration between many clinical investigators, funders and patient organisations.